2019
DOI: 10.6007/ijarped/v8-i2/5696
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of using Twitter Application in Teaching Pedagogy: A Meta-Synthesis Study

Abstract: In the new era of the borderless world, the development of pedagogical learning is growing and expanding progressively. Educators have diversified teaching methods to create interactive learning experiences. Twitter application is part of a social media network that is used by people every day. In the education world itself, Twitter application has been widely used in teaching pedagogy. Thus, this study is conducted to examine the effectiveness of using Twitter application in the teaching and learning process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Twitter is a popular social media platform (Lokman et al, 2019). It was introduced in 2006 and has gained popularity due to its micro-blogging and social media capabilities.…”
Section: Twitter and Student Engagementmentioning
confidence: 99%
See 2 more Smart Citations
“…Twitter is a popular social media platform (Lokman et al, 2019). It was introduced in 2006 and has gained popularity due to its micro-blogging and social media capabilities.…”
Section: Twitter and Student Engagementmentioning
confidence: 99%
“…In the context of education, Twitter has several unique features that facilitate effective delivery of information to students. These features include direct messaging, the 'tweet' function, link integration with other sources like videos, and an interesting interface (Lokman et al, 2019). Lecturers can use Twitter to notify and remind students about homework and assignments and share important and relevant resources (Umezulike & Nwagu, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A group of digital platforms made it easy for the student, the teacher, and the educational material to meet in one place, and this is considered one of the most important types and patterns of education that we live in these days [1]. However, the risks of cybersecurity through the use of these platforms have increased and their ways and impact have diversified, just as the impact of various threats on the environment of multiple platforms has remained a question that haunts all educational institutions, especially during the recent COVID 19 pandemic, in which the demand for using educational platforms increased, and then after the COVID 19 pandemic era, they became These institutions are unwilling to continue using these platforms because of their great influence and advantages that have made education an attractive sector for, all immediate indications indicate that we are in the era of synchronous digital education, but we must address the cybersecurity problems that threaten its continuity and ensure the safety of its workers and beneficiaries from students, teachers, assistant administrative staff, and an educational environment in order to ensure the safety of these platforms for more than a two billion learners and professors around the world [2], [3].…”
Section: Introductionmentioning
confidence: 99%
“…Presmeg (2006) suggested that visualization involves the creation of visual images which guide the creation of mathematical representations. The advancement of technology enables both teachers and students to benefit from technology (Lokman, Nasri & Khalid, 2019;Khalid, Karim & Husnin, 2018;Ruhil Amal, Nor Fariza & Affendi, 2017;George & Archontia, 2013;Khalid, Nawawi & Roslan 2009). In particular, technology assisted learning has been found useful to enhance children's learning (Bakar & Nasri, 2018).…”
Section: Introductionmentioning
confidence: 99%